INNV-17. INNOVATIVE EDUCATIONAL APPROACHES TO ENHANCE PATIENT AND CAREGIVER UNDERSTANDING OF TTFIELDS FOR GLIOBLASTOMA - Shackelford, Melissa (Neuro Oncol, 2019)
INTRODUCTION: The most common, aggressive malignant brain tumor is Glioblastoma (GBM) with patient median survival of 15–21 months. Patients with GBM face devastation of diagnosis, disease-burden, and hardship of seeking accurate information regarding treatment options. Evolving technology-enhanced methods of learning challenge traditional ways patients with cancer are educated and create an educational paradigm shift. The device manufacturer of Tumor Treating Fields (TTFields)) has developed innovative supplementary educational platforms to compliment healthcare provider (HCP) education of patients-caregivers with GBM treated with TTFields. This report aimed to evaluate these supplementary educational platforms. METHODS: Emerging technology methods were employed to address patient-caregiver frequently asked questions, which included queries regarding treatment overview, mechanism of action, treatment initiation, and management to potentially ease the emotional burden of patients-caregivers seeking TTFields information. The TTFields educational platforms included incorporation of Web program, Buddy Program, Open-House Program (live and webinar), Chalk-Talk Video, and Facebook. RESULTS: Educational platforms connecting potential and current TTFields patients-caregivers via live/webinar Open-House events ensured patient support. The phone-based Buddy Program allowed for direct 1:1 discussions between potential and current TTFields patients-caregivers. Patient-caregiver surveys revealed 100% would recommend the program to others (n=91); 98% were satisfied with the call experience (n=90); 76% felt the most valuable takeaway was speaking to someone who understands their situation (n=82). Of ambassadors, 98% felt they helped address registrants’ concerns (n=150). A dedicated TTFields Facebook page and first-ever, industry-led Facebook Live event (national broadcast; patients-caregivers discussed unique issues) were launched. Additionally, vignettes (eg, videos, written stories) were shared through a dedicated patient-caregiver website and YouTube channel. CONCLUSIONS: In an ever-growing information age, it is important that HCPs become aware of innovative ways to reach and provide education for patients with brain cancer. Emerging technology utilization may improve GBM supportive care, by improving communication channels and potentially easing burden.